OWNERSHIP OF INVASIVE FISH UNDER POSITIVE LAW IN INDONESIA - Mukhamad Fahminudin Alfiandi; Abdul Rokhim; Diyan Isnaeni (Pena Cendekia Insani, 2025)
This research focuses on analyzing the legal provisions for the ownership and import of invasive fish species in Indonesia, as well as the effectiveness of their implementation in protecting aquatic ecosystems from ecological threats. This research uses a juridical-normative approach with a qualitative analysis of applicable laws and regulations, a study of court decisions, and a review of scientific literature related to cases of the spread of invasive alien species (AIS). The results show that Indonesia has a fairly strong legal framework through Law Number 21 of 2019 concerning Quarantine and Law Number 31 of 2004 concerning Fisheries (as amended by Law Number 45 of 2009). However, weaknesses in implementation aspects, such as minimal supervision at water entry points, weak public legal literacy, and suboptimal coordination between institutions, remain major obstacles. This research implies the need to strengthen the quarantine system, implement multidimensional legal accountability (criminal, civil, and administrative), and develop a National Action Plan for Invasive Species Control based on scientific data as a long-term strategic step.